Gender Disparities in Receipt of HIV Testing Results in Six Sub-Saharan African Countries - Mulugeta Gebregziabher; Lin Dai; Caroline Vrana-Diaz; Abeba Teklehaimanot; Michael Sweat (Mary Ann Liebert, 2019)
Purpose: Receipt of HIV testing results is vital for individuals to know their status and make decisions that would improve their access to HIV prevention, treatment, and care. The objective of this study is to determine the association of HIV testing and receipt of results with three key exposure variables (HIV stigma, HIV knowledge, and media use) stratified by gender and country. Methods: Data from a random sample of adults aged 15?49 years from Burundi, Ethiopia, Kenya, Rwanda, Tanzania, and Uganda were abstracted from country-specific Demographic and Health Surveys or AIDS Indicators Surveys. Individuals were asked questions regarding demographics, socioeconomic status, sexual behaviors/attitudes, HIV knowledge, HIV stigma, and media-consumption. Weighted logistic regression was used to determine the association between receipt of HIV testing with key risk factors stratified by gender and country. Results: Gender disparities in HIV testing and receipt of results, HIV stigma, and HIV knowledge remain high. More women have recently tested for HIV and received their results than men. HIV stigma was associated with decreased recent HIV testing in all six countries for women, and for men except in Ethiopia, Tanzania, and Uganda. HIV knowledge was positively related to recent testing in all countries, except Uganda for women and Kenya and Tanzania for men. In Burundi and Rwanda, women had more HIV knowledge than men, while in Kenya, Ethiopia, Tanzania, and Uganda, men had more HIV knowledge than women. Conclusion: Given the importance of HIV testing for effective management of HIV in sub-Saharan Africa, it is crucial for these countries to exchange information on gender-specific policies and strategies that have the most impact on increasing HIV knowledge and decreasing HIV stigma.